Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

A method for quantifying feeding behavior of grass carp in outdoor ponds with complex backgrounds - Weiqiang Ni; Kang Wu; Lei Wang; Chenqing Zhang; Zequn Peng; Rong Tang; Zhangying Ye; Jian Zhao (Computers and Electronics in Agriculture, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

Sinocrassula zhaotongensis (Crassulaceae), a New Species From China - Ling‐Nan Wei; Jing Zhao; Jian‐Rong Zhang; Zi‐Xian Liu; Jia‐Guan Wang (New Zealand Journal of Botany, 2026)
Sinocrassula zhaotongensis , a new species of Crassulaceae from Yunnan Province, China, is described and illustrated. Morphologically, S. zhaotongensis is characterized by a glabrous plant surface, asymmetrically triangular to lanceolate basal leaves, triangular‐lanceolate sepals, and triangular petals that are yellowish at the base with dense purple‐red stripes and spots on the surfaces upward. Phylogenetic analyses based on concatenated chloroplast and nuclear DNA sequences strongly support S. zhaotongensis as a distinct lineage and sister to S. adpressa .

Investigation of In-Situ Shear Failure Mechanism of Rock and Acoustic Emission Characteristics Using Discrete Element Method - Long Chen; Jian-jun Huang; Ze Yang; Shun-chuan Wu; Shang-rong Wu; Yu-song Zhao (Applied Geophysics, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Association between plasma trace metals and non-alcoholic fatty liver disease among rural women in Southern China - Qiumei Liu; Xiaolin Li; Yufu Lu; Kaisheng Teng; Xiaoting Mo; Linhai Zhao; Songju Wu; Jiahui Rong; Qinyi Guan; Lei Luo; Tiantian Zhang; Yujian Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Integrating machine learning and prioritization to decipher the partitioning and risk of tire-derived chemicals in highly populated coastal regions - Nian-Nian Wu; Yuan Liu; Shan Liu; Ji-Xun Chen; Qin-Ge Zhou; Xiang-Rong Xu; Qing-Song Yang; Juan Ling; Jian-Liang Zhao (Water Research, 2026)

Priorities for enhancing resilience of SDG causal network from a human-nature perspective - Yiming Su; Guangjin Zhou; Mingyuan Wang; Xiaoyun Li; Tao Liang; Lingqing Wang; Jian Hu; Jixi Gao; Wenwu Zhao; Siyuan Tao; Peter E. Holm; Jörg Rinklebe; et al. (Resources, Conservation and Recycling, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Production of neofemales by 17β-estradiol and YY super-male breeding in northern snakehead (Channa argus) - Mi Ou; Yang Zhang; Rong Huang; Yaping Wang; Jianxiong Yin; Qing Luo; Kunci Chen; Haiyang Liu; Xincheng Zhang; Shuzhan Fei; Yuandong Sun; Baixiang Chen; et al. (Aquaculture, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Autonomic Nervous System Adaptation to Running in a Plateau Hypoxic Environment: Mechanisms and Prospects - Zhifeng Wang; Ting Shi; Shuangfeng Xu; Zhihui Hao; Jiao Yang; Huilan Zhao; Zongxu Liu; Jian Wang; Rong Zhao; Liwei Xing (Journal of Medical and Biological Engineering, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Induction of feline fetal fibroblasts into pluripotent stem cells using cat-derived reprogramming factors - Jian Qin; Nannan Sun; Yitong Wang; Jie An; Dipeng Zhao; Junling Li; Hao Zhang; Rong Du (Theriogenology, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

Inhibitory effects of different plant extracts on Histomonas meleagridis in vitro and in vivo in chickens - Qiao-Guang Chen; Shuang Wang; Jie Rong; Chen Chen; Zhao-Feng Hou; Dan-Dan Liu; Jian-Ping Tao; Jin-Jun Xu (Veterinary Parasitology, 2025)

Associations between plasma multi-metal exposure and mild renal impairment: Cross-sectional evidence of the potential mediating role of HDL-C in rural China - Kaisheng Teng; Qinyi Guan; Xiaoting Mo; Qiumei Liu; Lei Luo; Jiahui Rong; Tiantian Zhang; Wenjia Jin; Linhai Zhao; Songju Wu; Jiansheng Cai; Zhiyong Zhang; et al. (Toxicology and Applied Pharmacology, 2025)

Association of multi-metal exposure with hyperuricemia in middle-aged and older adults: A cross-sectional study in rural Guangxi, China - Qinyi Guan; Kaisheng Teng; Qiumei Liu; Songju Wu; Lei Luo; Linhai Zhao; Jiahui Rong; Wenjia Jin; Tiantian Zhang; Mo Xiaoting; Cai Jiansheng; Zhiyong Zhang; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Record high CH4/N2 adsorption separation selectivity in a scalable metal-organic framework - Yan-Long Zhao; Xuefeng Bai; Xin Zhang; Zhang-Ye Han; Jian-Rong Li (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Relationship between physicochemical properties, non-volatile substances, and microbial diversity during the processing of dry-cured Spanish mackerel - Shanyu Wang; Chong Jian; Ling Zhao; Huihui Sun; Qi Liu; Rong Cao (Food Research International, 2025)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Identification and analysis of MAPK cascade gene families of Camellia oleifera and their roles in response to cold stress - Kaifeng Xing; Jian Zhang; Haoxing Xie; Lidong Zhang; Huaxuan Zhang; Liyun Feng; Jun Zhou; Yao Zhao; Jun Rong (Molecular Biology Reports, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

PoIL8-L, a teleost interleukin-8 like, enhances leukocyte cellular vitality and host defense against bacterial infections in Japanese flounder (Paralichthys olivaceus) - Kun-yu Zhao; Yue Fang; Rong-jing Xu; Jian Zhang; Bin Sun; Xue-peng Li (Fish & Shellfish Immunology, 2024)

Role of NF-κB signaling pathway in H2O2-induced oxidative stress of hiPSCs - Jian Qin; Jie Yang; Jun Li; Dipeng Zhao; Jie An; Zhuhui Zhai; Hejie Wang; Junling Li; Minmin Dou; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2024)

Decapod iridescent virus 1 (DIV1) 168L can target cuticle protein 8 from Litopenaeus vannamei - Qin Zheng; Huan-huan Rao; Fu-Rong Zhao; Xiao-Juan Chen; Wei Wang; Jian-Ming Chen (Journal of Invertebrate Pathology, 2024)

Construction of large-aperture mesoporous silica spheres supported polyoxometalate heterogeneous catalysts and their high-efficiency for the ultra-deep desulfurization - Jia-Qi Wu; Lu-lu Ma; Zhuang-Zhuang Li; Xin Li; Si-Wen Li; Chang Li; Rong-Xi Li; Jian-She Zhao (Fuel, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

A 3,5-dinitropyridin-2yl Substituted Flavonol-based Fluorescent Probe for Rapid Detection of H2S in Water, Foodstuff Samples and Living Cells - Lai-Xin Hong; Rong-Lan Zhang; Jian-She Zhao (Journal of Fluorescence, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Molecular Cloning and Characterization of Scavenger Receptor Class B Type 1 in Grass Carp (Ctenopharyngodon idellus) and Its Expression Profile following Grass Carp Reovirus Challenge - Yang Zhang; Jiayuan Shi; Yuntao Lu; Qing Luo; Pengfei Chu; Rong Huang; Kunci Chen; Jian Zhao; Yaping Wang; Mi Ou (Fishes, 2024)
As a member of the pattern recognition receptor (PRR) class, scavenger receptor class B type 1 (SRB1) plays a key role in innate immunity. Grass carp (Ctenopharyngodon idellus) ranks among the most extensively cultivated freshwater aquaculture species in China. However, little is known about the function of SRB1 in C. idellus. In this research study, a SRB1 gene was identified in C. idellus, named CiSRB1. The full-length cDNA of CiSRB1 is 2486 bp long, with an open reading frame (ORF) of 2486 bp encoding a 497 amino acid (aa) protein containing a conserved CD36 domain. The identified genomic DNA length of CiSRB1 is 20,042 bp, including 12 exons and 11 introns. The predictive analysis of protein interactions revealed that CiSRB1 could interact with the outer capsid proteins of typical GCRV strains. The tissue distribution of CiSRB1 exhibited age-dependent characteristics. CiSRB1 displayed the highest expression in the intestines and moderate levels in muscle, spleen, liver, and brain of one-year-old grass carp while maintaining relatively low levels in three-year-old grass carp. Following grass carp reovirus (GCRV) infection, notable upregulation of CiSRB1 transcripts was observed in major immune tissues (gills, intestines, spleen, and liver). Furthermore, significant differences were found between one-year-old and three-year-old grass carp, with lower CiSRB1 expression levels being detected in the older group. Additionally, a distinct response to GCRV infection was observed in one-year-old and three-year-old grass carp. It was found that one-year-old individuals had a mortality rate of up to 84% 6 days post-infection (dpi), whereas all three-year-old counterparts survived after GCRV infection. The analysis of GCRV copy numbers across tissues revealed substantially higher levels in one-year-old grass carp compared with their older counterparts, confirming the existence of age-dependent susceptibility to GCRV infection in grass carp. Combined with these results, it was speculated that the decline in cell-surface CiSRB1 expression with age may impede reovirus binding to host cells, potentially explaining why older grass carp demonstrated enhanced resistance to GCRV infection. This observation accentuates the importance of CiSRB1 in the context of GCRV infection and provides insights into age-dependent susceptibility to reovirus.

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Multiple Applications of a Novel Fluorescence Probe with Large Stokes Shift and Sensitivity for Rapid H2S Detection - Lai-Xin Hong; Le Sun; Cong Li; Rong-Lan Zhang; Jian-She Zhao (Journal of Fluorescence, 2024)

An appetite assessment method for fish in outdoor ponds with anti-shadow disturbance - Weiqiang Ni; Dan Wei; Zequn Peng; Zhen Ma; Songming Zhu; Rong Tang; Xuelei Tian; Jian Zhao; Zhangying Ye (Computers and Electronics in Agriculture, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

A new 1,4-benzoxazine derivative produced by endophytic Colletotrichum gloeosporioides B-142 - Bing Zhang; Zhi-pu Huang; Yu Si; Ke-tao Zhang; Xiao-rong Xu; Jian-hong Chen; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Effect of topographic slope on the interaction between debris flows and riparian forests - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Dong-ri Song; Wan-yu Zhao; Ke Jin (Landslides, 2024)

Mid-Neoproterozoic (ca. 845 Ma) metamorphism of the southwestern Yangtze Block and its tectonic implications - Zhao Yang; Peter A. Cawood; Jian-Wei Zi; Long-Long Gou; Gui-Chun Liu; Rong Liu; Xiao-Fei Xu (Precambrian Research, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

The space-charge region at NiFe-MOF⊆LDH p-n junction by self-sacrificing LDH to boost oxygen evolution tandem with in-situ electro-Fenton - Na Zhang; Shi-Xian Guan; Qing Zhang; Jia-Rong Zhao; Jian-Yong Zhang; Qin-Fei Ke; Yong-Zheng Fang (Chemical Engineering Journal, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

The carbon footprint response to projected base stations of China's 5G mobile network - Xiaodong Zhang; Philippe Ciais; Xiaohu Jian; Xinrui Liu; Rong Wang; Kaijie Chen; Yufei Huang; Tao Huang; Hong Gao; Yuan Zhao; Jianmin Ma (Science of The Total Environment, 2023)

Photocatalysis-self-Fenton system over edge covalently modified g-C3N4 with high mineralization of persistent organic pollutants - Tongbin Lu; Hui Zhao; Liang Jian; Rong Ji; Chengsi Pan; Guangli Wang; Yuming Dong; Yongfa Zhu (Environmental Research, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Mechanical and microscopic properties of soil according to the rate of increase in pore water pressure - Zhao Duan; Zhen-Yan Li; Yan-Bin Wu; Bing Niu; Rong-Jian Shen (Soil and Tillage Research, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Carbonate nanophase guided by terminally functionalized polyisoprene leading to a super tough, recyclable and transparent rubber - Mo-Kun Chen; Yi-Hai Zhao; Rong Zhang; Ying Yang; Jian Cao; Mao-Zhu Tang; Guangsu Huang; Yun-Xiang Xu (Chemical Engineering Journal, 2023)

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Microstructural Differences of the Cerebellum-Thalamus-Basal Ganglia-Limbic Cortex in Patients with Somatic Symptom Disorders: a Diffusion Kurtosis Imaging Study - Liao Dong; Huai-Bin Liang; Jiaxin Du; Yingying Wang; Qichen Zhou; Ziyue Xin; Yue Hu; Yi-Sheng Liu; Rong Zhao; Yuan Qiao; Chenglin Zhou; Jian-Ren Liu; et al. (The Cerebellum, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

CuO Nanoparticle Exposure Impairs the Root Tip Cell Walls of Arabidopsis thaliana Seedlings - Guangli Nie; Jian Zhao; Rong He; Yulin Tang (Water, Air, & Soil Pollution, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Two new benzophenones from endohydric moss Polytrichum Commune - Xu-Hong Duan; Jian-Cheng Zhao; Lin Li; Lin Pei; Pei He; Rong Wang (Natural Product Research, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Genetic diversity and population structure of the northern snakehead (Channa argus Channidae: Teleostei) in central China: implications for conservation and management - Ruo-Jin Yan; Gui-Rong Zhang; Xiang-Zhao Guo; Wei Ji; Kun-Ci Chen; Gui-Wei Zou; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics, 2018)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Personal exposure to PM2.5 associated with heavy metals in four travel modes of Tianjin during the summer season - Bao Qing Wang; Jian Feng Liu; Bo Wei Liu; Hong Hong Niu; Rong Hui Chen; Ze Bei Wang; Jia Jia Zhao; Zi Hui Ren (Environmental Science and Pollution Research, 2017)

Streptomyces xiangtanensis sp. nov., isolated from a manganese-contaminated soil - Ping Mo; Yi-Zun Yu; Jia-Rong Zhao; Jian Gao (Antonie van Leeuwenhoek, 2017)

Identification of a New Rice Low-Tiller Mutant and Association Analyses Based on the SLAF-seq Method - Yan Li; Xiao-Fang Zeng; Yi-Chen Zhao; Jian-Rong Li; De-Gang Zhao (Plant Molecular Biology Reporter, 2017)

Isolation and characterization of twenty-one polymorphic microsatellite loci from Schizothorax o’connori and cross-species amplification - XIANG-ZHAO GUO; GUI-RONG ZHANG; KAI-JIAN WEI; SHAN-SHAN GUO; JIAN-HUI QIN; Jonathan P. A. GARDNER (Journal of Genetics, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Two new bicyclic sesquiterpenes from the stems of Kadsura heteroclita - Wei Su; Jian-Ping Zhao; Jian Hu; Min Yang; Melissa Jacob; Xiong Cai; Rong Zeng; Sheng-Huang Chen; Hui-Yong Huang; Ikhlas Khan; De-An Guo; Wei Wang (Natural Product Research, 2014)

Systemic Evaluation of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Ai-Hua Zhu; Yan-Rong Hu; Wei Liu; Feng Gao; Jian-Xin Li; Li-Hui Zhao; Gang Chen (Cell Biochemistry and Biophysics, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite loci for the Lhasa schizothoracin Schizothorax waltoni - Xiang-Zhao Guo; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Rui-Bin Yang; Jonathan P. A. Gardner; Qi-Wei Wei (Conservation Genetics Resources, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Isolation and characterization of twenty-four polymorphic microsatellite loci in Oxygymnocypris stewartii - Shan-Shan Guo; Gui-Rong Zhang; Xiang-Zhao Guo; Kai-Jian Wei; Jian-Hui Qin; Qi-Wei Wei (Conservation Genetics Resources, 2013)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

Comparison of metabolic effects of ziprasidone versus olanzapine treatment in patients with first-episode schizophrenia - Jian-Jun Ou; Yi Xu; Hong-Hui Chen; Xiaoduo Fan; Keming Gao; Juan Wang; Xiao-Feng Guo; Ren-Rong Wu; Jing-Ping Zhao (Psychopharmacology, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Arachnoid cell involvement in the mechanism of coagulation-initiated inflammation in the subarachnoid space after subarachnoid hemorrhage - Zhao-liang Xin; Xiao-kang Wu; Jian-rong Xu; Xi Li (Journal of Zhejiang University-SCIENCE B, 2010)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Secretion of malate and citrate from roots is related to high Al-resistance in Lespedeza bicolor - Xiao Ying Dong; Ren Fang Shen; Rong Fu Chen; Zhao Liang Zhu; Jian Feng Ma (Plant and Soil, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

The promoter of a rice glycine-rich protein gene, Osgrp-2, confers vascular-specific expression in transgenic plants - Zong-Zhi Liu; Jian-Long Wang; Xun Huang; Wei-Hui Xu; Zhao-Ming Liu; Rong-Xiang Fang (Planta, 2003)